A functional study of ground stone tools from the Bronze Age site of Dingjiacun in South China: Based on use-wear evidence. (December 2021) - Chen, Hong; Xue, Liping; Chen, Ran; Si, Hongwei; Jin, Yao; Tang, Yixue
Highlights: A large sample of ground stone tools from Dingjiacun site in Jingsu, China was studied. Use-wear analysis is adopted to investigate the function of the tools. Ground stone tools were used for wood-working, harvesting, earth-working, and hunting. The Dingjiacun site once contained a settled agricultural community. Abstract: Ground stone tools were a revolutionary technology that appeared during the Late Pleistocene and Early Holocene periods and played a key role in the economic and ritual activities of many prehistoric and early historic societies. Previous functional analyses of ground stone tools in China have focused primarily on Neolithic materials and had a regional preference for northern China. This article reports on the results of a functional study of an assemblage of ground stone tools found at the Dingjiacun site in southern China. Use-wear analysis was adopted to interpret the tools' function through observing and identifying the wear patterns that corresponded to different substantial activities. Our results showed that the site once contained a settled agricultural community where a large array of activities such as wood-working, harvesting, earth-working, and hunting were carried out. The results of our study should provide a better understanding of human behaviors and subsistence strategies in the Lower Yangtze River region during the Bronze Age.